Parametric Study of Fuzzy Number Linear Programming - Yan-Lin Jia; Yan Yang; Yi-Hua Zhong (2013 Ninth International Conference on Computational Intelligence and Security, 2013)
This paper is devoted to show the effect of the continuous variational parameter in the objective function coefficients on the optimum solution, which is an extension of the sensitivity analysis of fuzzy number linear programming. We prove that if the parameter is in a certain range, this problem has a unique optimal solution, otherwise it has non-unique optimal solutions or is unbounded or infeasible. Then, the optimal value function is a fuzzy linear function of the parameter. Finally, numerical examples demonstrate the theorem and illustrate the computational procedure.